Knee extensor muscle weakness and radiographic knee osteoarthritis progression: The influence of sex and malalignment. (4th July 2018) - Dell'isola, Andrea; Wirth, Wolfgang; Steultjens, Martijn; Eckstein, Felix; Culvenor, Adam G
Abstract : Background and purpose — Knee extensor (KE) muscle weakness is a modifiable feature commonly observed in individuals with knee osteoarthritis (KOA) and constitutes a potential target for patient-specific interventions. Therefore, in this study, we explored whether KE weakness is associated with radiographic (medial and/or lateral) KOA progression and how this relationship differs depending on frontal plane knee alignment and sex. Patients and methods — We studied 3, 075 knees (1, 961 participants, 58% female) from the Osteoarthritis Initiative with radiographic Kellgren–Lawrence grade 1–3. Peak KE torque (Nm/kg) was assessed at baseline, and progression defined as fixed-location joint space width loss (≥ 0.7mm) in medial and lateral tibiofemoral compartments from baseline to 4-year follow-up. Knee-based generalized estimating equations, stratified by alignment (malaligned vs. neutral), estimated the relative risk (RR) of progression for those in the lowest (and middle) vs. highest KE torque group (split by tertiles). Secondary analyses explored whether this relationship was compartmental- or sex-specific. Results — Being in the lowest (or middle) compared with the highest torque group increased the risk of progression in neutrally aligned knees (relative risk [RR] 1.2 [95% CI 1.0–1.4]; and 1.2 [CI 1.0–1.4], respectively), but not after adjusting for age, sex, BMI, pain, and radiographic severity. In secondary analyses, women with neutral alignment in the lowest compared with the highest torque group had significantly increased risk of lateral compartment progression independent of age, BMI, disease severity, and pain (RR 1.3 [CI 1.0–1.8]). No association was observed between KE torque and KOA progression in men, irrespective of alignment. Interpretation — These results identify a potentially important clinical phenotype: KE weakness may be a more important risk factor for radiographic KOA progression in women without knee malalignment.